HDAC6 Interacts With Poly (GA) and Modulates its Accumulation in c9FTD/ALS - del Rosso, Giulia; Carlomagno, Yari; Todd, Tiffany W.; Jones, Caroline Y.; Prudencio, Mercedes; Daughrity, Lillian M.; Yue, Mei; Jansen-West, Karen; Tong, Jimei; Shao, Wei; Wu, Yanwei; Castanedes-Casey, Monica; et al. (Frontiers in Cell and Developmental Biology, 2022)
The aberrant translation of a repeat expansion in chromosome 9 open reading frame 72 (C9orf72), the most common cause of frontotemporal dementia (FTD) and amyotrophic lateral sclerosis (ALS), results in the accumulation of toxic dipeptide repeat (DPR) proteins in the central nervous system (CNS). We have found that HDAC6 specifically interacts with the DPR poly(GA) and co-localizes with inclusions in both patient tissue and a mouse model of this disease (c9FTD/ALS). Overexpression of HDAC6 increased poly(GA) levels in cultured cells independently of HDAC6 deacetylase activity, suggesting that HDAC6 can modulate poly(GA) pathology through a mechanism that depends upon their physical interaction. Moreover, decreasing HDAC6 expression by stereotaxic injection of antisense oligonucleotides significantly reduced the number of poly(GA) inclusions in c9FTD/ALS mice. These findings suggest that pharmacologically reducing HDAC6 levels could be of therapeutic value in c9FTD/ALS.